Measurement of Acceleration Due to Gravity Using Arduino - Bedi, Raunak (Journal of Biology and Life Science, 2024)
The undertaken research paper is an easy experiment based on Arduino was constructed in order to investigate the acceleration of the object while it was falling freely and to estimate the value of "g" (the acceleration that is generated by gravity). The reseach aimed to achieve three objectives through this research: first, to comprehend the manner in which airborne gravity gradiometers synthesise gravity fields using residual terrain modelling and the equivalent source layer method; second, to evaluate the durability of systems based on Arduino in various environments; and third, to contrast the accuracy, efficiency, and user-friendliness of these systems with those that are more conventional. The investigation of the acceleration due to gravity measurement using Arduino was conducted using secondary sources, which include books, websites, academic papers, newspapers, and magazines. These sources are not directly comparable. The evaluation and severity determination of a diverse array of research topics are facilitated by this explanatory research approach to the analysis of the conceptual components. The result of the study implies that in order to obtain distance time curves, readings realted to gravity is made at a variety of intervals throughout the course of application of the traditional kinematic equations made it possible to compute the acceleration that happened during the free fall. There has been found to be a good agreement between “the shape of the distance-time graphs” that were gathered from the secondary setup and the graphs that were expected, and the values of g that were calculated were within the range that was anticipated. It has been further discovered that the magnitude of gravitational acceleration is 9.805 metres per second squared after a series of research study were carried out.